2009
DOI: 10.1002/sia.3109
|View full text |Cite
|
Sign up to set email alerts
|

XPS study of early stages of Al/Au interface formation

Abstract: The interface formation between Au polycrystalline substrate kept at temperature of liquid nitrogen and Al deposit and its evolution during sample thermal treatments have been investigated by means of XPS. The intermixing of the Al and Au atoms at the interface occurred readily already at temperature of liquid nitrogen and resulted in the appearance of well-resolved components on the high-binding-energy side of the Au(4f) spectra assignable to AlAu intermetallic phase. The sample annealing resulted in the grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 22 publications
(26 reference statements)
1
5
0
Order By: Relevance
“…The binding energy shift ( ~ 1.5 eV) of Au(4f 7/2 ) line of the alloy phase formed at Al/Au interface is close to the value corresponding to the bulk AlAu intermetallic [11][12][13]. The formation of AlAu bimetallic phase at Al/Au interface at the temperature of liquid nitrogen can be explained on the base of its thermodynamic stability [20].…”
Section: Intermetallic Growth and Phase Transformationssupporting
confidence: 56%
“…The binding energy shift ( ~ 1.5 eV) of Au(4f 7/2 ) line of the alloy phase formed at Al/Au interface is close to the value corresponding to the bulk AlAu intermetallic [11][12][13]. The formation of AlAu bimetallic phase at Al/Au interface at the temperature of liquid nitrogen can be explained on the base of its thermodynamic stability [20].…”
Section: Intermetallic Growth and Phase Transformationssupporting
confidence: 56%
“…Thus, the new doublets are due to the interaction between the core of Au-2NT NPs and Al. The Au 4f XPS spectra of Au-2NT NPs deposited with Al are similar to those of Au-Al alloys [112][113][114][115][116]. The shift of the Au 4f bands to higher binding energy is attributed to the "charge-compensation model".…”
mentioning
confidence: 60%
“…The Au 4f XPS spectra of Au-2NT NPs deposited with Al are similar to those of Au-Al alloys. [112][113][114][115][116] The shift of the Au 4f bands to higher binding energy is attributed to the ''charge-compensation model''. The charge transfer between Au and Al leads to a dramatic d electron depletion from Au sites, so that the attraction between the Au nucleus and the 4f electrons becomes stronger.…”
Section: Mechanism For the Resistive Switchesmentioning
confidence: 99%
“…Since lattice strain occurs at surface skin up to a few atomic layers, an additional depression of the potential well takes effect on the BE of the core electrons. For Cu 18 and Ni 18 atomic clusters, calculations [37] suggested that the BE for both the initial and the final states undergo positive shifts from zero to 0.7 ~ 0.8 eV when the average strain of the clusters are increased from zero to 6%. An atomic layer-resolved XPS of Ni surface [40] revealed that the surface under-coordinated atoms.…”
Section: Discussion On Size Dependent Be Shiftmentioning
confidence: 99%
“…Similar BE shift has also been observed in many other under-coordinated systems including terrace edge, adatoms, vacancies and interface of alloy. [17][18][19][20][21][22][23][24] However, the origin of the BE shift which corresponds to the nature of bonds and electrons annexed under-coordinated atoms has been under debates with following possible mechanisms:…”
Section: Overviewmentioning
confidence: 99%